Financial management efficiency of islamic boarding school based on information technology - Romi Fadillah Rahmat; Seniman; Sawaluddin; Arisandi, Dedy (Talenta Publisher, 2021)
Utilization of information technology is a very important requirement for every component of society. Easy, fast and accurate data and information access can optimize routine daily work. Mawaridussalam Islamic boarding school Batang Kuis as an Islamic education institution that plays a role in shaping the character and personality of the next generation of the nation is expected to be able to optimally manage finances and provide good service to the academics of the Islamic boarding school. Until now, financial management is still done manually using bookkeeping, there is no specific financial application used in Islamic boarding school financial management, so it is difficult and slow in recording, processing, controlling and reporting financial activities. Based on these problems, an application is needed that can be used by the treasurer and board of boarding school leaders for financial management systematically. The method applied is the User Centered Design approach and the target that was successfully achieved is the availability of web-based financial management applications that are used properly to increase the efficiency and effectiveness of financial management in Islamic boarding schools.